Analisis Kadar Vitamin C Bawang Putih Majemuk Bawang Hitam dan Bawang Putih Tunggal Serta Aktivitas Antioksidan dengan Metode ABTS - Adhiva Berlian Febryanti; Danang Raharjo; Septian Maulid Wicahyo (Jurnal Kesehatan Amanah, 2025)
Antioxidants are compounds that can neutralize free radicals and inhibit the continuation of oxidation processes that may cause cellular damage. Vitamin C acts as an antioxidant by protecting biological molecules from oxidative stress. Garlic, both compound and single types, as well as black garlic, are known to contain vitamin C and play a significant role as natural antioxidants in combating free radicals that can damage cells and body tissues. This study aimed to determine the vitamin C content and antioxidant activity of compound garlic (Allium sativum L.), black garlic, and single garlic (Allium sativum L.). The vitamin C content was measured using UV-Vis spectrophotometry, while antioxidant activity was evaluated by the ABTS method, expressed in IC₅₀ values. The results showed that black garlic extract had the highest vitamin C content of 51.516 mg/100 g. In the ABTS assay, black garlic also demonstrated the lowest IC₅₀ value of 25.99 μg/mL, indicating a very strong antioxidant activity. These findings suggest that the fermentation process of garlic into black garlic significantly increases its vitamin C levels as well as enhances its antioxidant properties. Therefore, black garlic has great potential to be developed as a natural antioxidant source, contributing to the prevention of oxidative stress-related cellular damage and supporting overall health